2018
DOI: 10.1002/ceat.201800362
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Biogas Plant Realizations

Abstract: A techno‐economic analysis for four different types of biogas plant realizations was performed, including one biogas biorefinery concept. For each concept detail, a process flow diagram was created. Mass and energy balances were estimated. The net present value and payback were calculated for each concept for a better feasibility understanding. The results showed that with the used expensive substrate, namely, wheat straw, the obtained paybacks appeared to be more than 100 years. Sensitivity analysis was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…where C e is the cost of the equipment ($); a and b are cost constants, which value depends on the equipment being evaluated; S is a size parameter, obtained from the simulation that depends on the equipment that is being evaluated; and n is an exponent that also depends on the equipment. The values obtained from this method were estimated using carbon steel as a material to update this value and use it for stainless steel; this method has been previously used to evaluate biorefinery plants [36][37][38]. Using Equation (1), we estimated the inside battery limits (ISBL), which consider all the equipment used in the flowsheet, to estimate the outside battery limits (OSBL), wherein a factor of 0.5 of the ISBL was chosen.…”
Section: Economic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…where C e is the cost of the equipment ($); a and b are cost constants, which value depends on the equipment being evaluated; S is a size parameter, obtained from the simulation that depends on the equipment that is being evaluated; and n is an exponent that also depends on the equipment. The values obtained from this method were estimated using carbon steel as a material to update this value and use it for stainless steel; this method has been previously used to evaluate biorefinery plants [36][37][38]. Using Equation (1), we estimated the inside battery limits (ISBL), which consider all the equipment used in the flowsheet, to estimate the outside battery limits (OSBL), wherein a factor of 0.5 of the ISBL was chosen.…”
Section: Economic Assessmentmentioning
confidence: 99%
“…However, they exhibit a strong dependence on the size of the plant, reaching a value even higher than the initial investment cost. H 2 O ($/m 3 ) 1.9 [37] NaOH ($/t) 400 [38] Ca(OH) 2 ($/t) 131.8 [36] Algae ($/t) 21 [39] With the estimation of the costs and revenues, it was possible to calculate the net present value (NPV) of the plant. This parameter has been widely used for the economic assessment of plant investments and was used in this study [42][43][44][45].…”
Section: Economic Analysismentioning
confidence: 99%
“…The Chemical Plant Cost Index (CEPCI) used is 540. A typical formula for purchased equipment cost [18] estimation is 1) C e ¼ a þ bS n…”
Section: Techno-economic Backgroundmentioning
confidence: 99%
“…From previous studies [1], where different types of biogas plants (conventional, biogas upgrade, intensified) were analyzed, it was concluded that biogas plants without subsidies are not economically feasible. Thus, an attempt was made to diversify the production of a biogas plant and to increase the revenue by another key-product; in other words, to rearrange the biogas plant into a biorefinery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation